THE ANALYSIS OF EMOTIVE FUNCTION IN KELLEY ARMSTRONG’S “THE RECKONING” - St. Salmah Bahar; Sardian Maharani Asnur (UIN Alauddin Makassar, 2014)
ABSTRACT This thesis studied about the analysis of emotive function in Kelley Armstrong’s novel “The Reckoning”. The thesis aims to find out and to explain the emotive function performed by the main character in the novel. The writer used descriptive qualitative method to describe and explain the emotive function in the novel. The instrument which is used by the writer was note-taking. Along this instrument, the writer read the novel, then taking seven colors of cards to write the emotive function on the novel, after that the expression is written down and classified the emotive function from the novel. In spite of, the writer analyzed the data by using Roman Jakobson’s theory. Through this analysis, the writer found seven kinds of emotive function; those were displeasure that have 5 expressions or 4,351%, displeasure that have 3 expressions or 2,366 %, like that have 2 expressions or 1,386%, dislike that have 7 expressions or 6,346%, worry that have 8 expressions or 7,344%, desire that have 3 expressions or 2,366%, and gratitude that have 3 expressions or 2,366%. The emotive function mostly used in the conversations on the novel was the expressions of worry. Furthermore, one expression thatis used by the main character may have more than one function of emotive based on the context.